2008
DOI: 10.1029/2008ja013220
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electron precipitation during substorm injection events: High‐latitude fluxes and an unexpected midlatitude signature

Abstract: [1] Geosynchronous Los Alamos National Laboratory (LANL-97A) satellite particle data, riometer data, and radio wave data recorded at high geomagnetic latitudes in the region south of Australia and New Zealand are used to perform the first complete modeling study of the effect of substorm electron precipitation fluxes on low-frequency radio wave propagation conditions associated with dispersionless substorm injection events. We find that the precipitated electron energy spectrum is consistent with an e-folding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 43 publications
9
87
0
Order By: Relevance
“…Only by using multiparameter and multi‐instrument observations of the ionization changes produced by EEP is it possible to accurately characterize the EEP events. The combination of ground‐based and satellite measurements provides the clearest morphology of EEP characteristics, and this work builds on previous studies of this kind [e.g., Clilverd et al , 2008, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only by using multiparameter and multi‐instrument observations of the ionization changes produced by EEP is it possible to accurately characterize the EEP events. The combination of ground‐based and satellite measurements provides the clearest morphology of EEP characteristics, and this work builds on previous studies of this kind [e.g., Clilverd et al , 2008, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, EEP from a substorm injection occurs near midnight magnetic local time (MLT), with the precipitation region (in the ionosphere) rapidly expanding eastward with velocities that correspond to electron drift velocities associated with energies of 50–300 keV [ Berkey et al , 1974]. The electron energies involved in substorm injections seen by satellites such as LANL are typically 50–1000 keV, with the highest fluxes occurring at the lowest energies [ Baker et al , 1985; Clilverd et al , 2008]. While the satellite observations provide some information on the energy spectra of the injected electrons and the fluxes in drift orbit, it is very difficult to determine what proportion of the electrons are being precipitated into the atmosphere through onboard satellite measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As documented previously, the electron integral energy spectrum can be fitted to a power law at high energies [Xiao et al, 2008;Clilverd et al, 2008Clilverd et al, , 2012. For a power law index of Àn, it can be shown that…”
mentioning
confidence: 99%
“…Although [26] mention electron energies up to 400 keV, we follow [27] with a mean energy of 100 keV. The second one is a mean case with E= 10 keV.…”
Section: Influence Of the Precipitationmentioning
confidence: 99%